Analisa Faktor-Faktor yang Berhubungan dengan Kejadian Mioma Uteri di RSUD dr. Adhyatma Semarang - Yosi Apriyani; Sri Sumarni (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2013)
One reproductive problems experienced by women of childbearing age is a uteri-ne tumor. These are most related to reproduction which is myoma uterine. In Indonesia, myoma uterine was found from 2.30 to 11.7 % of all gynecological patients treated. The risk factors such as age, parity, age of menarche and menstrual status can lead to uterine myoma. This study aimed to determine the incidence of the risks of uterine myoma factors which consist of age, parity, age at menarche and menstrual status at dr.Adhyatma Hospital of Semarang. This study uses a quantitative research design with a retrospective approach. The data was a secondary data. The population is women who suffered from myoma uterine which were treated at dr Adhyatma Hospitals during a year in 2012. The sample involved in this study was 40 people. The analysis which was used in this study is frequency and an odds ratio analysis. The results of this study stated that women with age climacterium or menopause had 1.3 times the risk of having myoma submukosum than reproductive age ( OR = 1.333 and 95 % CI = 0.350 to 4.933 ). Multiparous / grandemultipara women have 2.7 times the risk of having myoma submukosum than women with nulliparous / primiparous women ( OR = 2.786 and 95 % CI = 0.773 to 10.043 ). Early age of menarche has 2 times risks of having myoma submukosum than women with normal age of menarche ( OR = 2.000 and 95 % CI = 1.455 to 2.749 ). Th menstrual status is not a risk factor submukosum myomas ( OR = 0.675 and 95 % CI = 0.194 to 2.352 ). The conclusion of this study is that risk factors such as age climacterium, parity multiparous / grandemultipara, early menarche is a factor that can increase the risk of uterine myomas.